(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2001)
Indonesian people as human resources should be prepared to globalization era in the 21st century, therefore they have to develop their higher order thinking skill rapidly, to improve their quality. Science education has an important role to develop young generation thinking skill, that makes science teachers training needs to be improved. Three science teaching models have been developed to increase science teacher candidates high order thinking skill, consist of Chemical Bond Model of Teaching (MPIK), Thermodynamics Model of Teaching (MPTD) and Anatomy and Physiology of Human Body Model of Teaching (MPAF). Each of the models consists of concept analysis and concept map, learning activities, teaching materials, test item. These studies show the dependency of the higher order thinking aspects and the characteristics of the subject matter in the models, including kind of concepts, width and depth of the subject matter areas. The models have been implemented and evaluated in three institutes of teacher training in Java. The findings show that the models had successfully increased the science teacher candidates way of thinking, on the whole stages of critical thinking skills, that have raised their propositional and combinatorial thinking. The impact shows that science models of learning (MPIPA) are available as new trend of science teacher training for the globalization era.